Eficiência de diferentes produtos fungicidas no controle da antracnose em manga - Silva, George Fagner da (2008)
Anthracnosis is a serious disease that limits the production of healthy and marketable mangos (Mangifera indica). Due to the serious nature of this disease, a study was undertaken to test the efficacy of azoxystrobin as compared to different fungicides commonly utilized for the control of this disease, in two experiments. Each experiment consisted of ten treatments with four replicates. The plots were consisted of three plants of cv. Tommy Atkins. The products tested were azoxystrobin + difenoconazole WG (200; 300; 400 e 600 mL ha-1p.c.); azoxystrobin (120 mL ha-1p.c.); chlorothalonil WP (1500 e 2000 mL ha-1p.c.); difenoconazole (300 e 500 mL ha-1p.c.), and an unsprayed control. A total of four applications were performed at 15 days intervals, the first one performed at panicle plain flux. 40 days after the last application were collected 25 fruits for plot. The same ones were conditioned in cardboard boxes and stored at ambient temperature during 15 days, when the evaluated of anthracnosis incidence was accomplished. In the first experiment, the with azoxystrobin in its composition didn t differ between then. In the second experiment, the treatments with fungicides were similars, althought these had differed from the unsprayed control. The analysis of regression pointed azoxystrobin + difenoconazole 600 mL ha-1p.c. as the most efficient in the control of anthracnosis in both experiments